Comparison of the image quality of turbo spin echo- and echo-planar diffusion-weighted images of the oral cavity. Issue 19 (May 2018) - Hirata, Kenichiro; Nakaura, Takeshi; Okuaki, Tomoyuki; Kidoh, Masafumi; Oda, Seitaro; Utsunomiya, Daisuke; Namimoto, Tomohiro; Kitajima, Mika; Nakayama, Hideki; Yamashita, Yasuyuki
Abstract : Abstract: The purpose of this study was to compare the image quality of turbo spin echo (TSE) diffusion-weighted imaging (DWI) and echo-planar imaging (EPI) of the oral cavity region. This retrospective study included 26 patients who had undergone both TSE- and EPI-DWI. Misregistration of DWI with T2-TSE images was assessed in the oral cavity. We also compared geometric distortion, the signal-to-noise ratio (SNR), contrast, and the apparent diffusion coefficient (ADC) for the tongue parotid gland, and spinal cord. On a 5-point scale, 2 radiologists scored the TSE- and EPI-DWI of each patient for ghost artifacts, image contrast, and overall image quality. Distortion in the phase-encoded direction was significantly lower on TSE- than EPI-DWI. The SNR of the tongue and parotid gland was significantly higher on TSE than EPI-DWI except spinal cord. No significant difference was found in contrast and ADC values (except for the ADC of tongue). TSE-DWI yielded higher qualitative scores for all parameters except image contrast. For the oral cavity region, TSE-DWI was superior to EPI-DWI with respect to distortion-free images and superior image quality.